Studies on HSAG, a middle repetitive family of genetic elements which elicit a leukemia-related cellular surface antigen. - Beitel, L K (1986)
HSAG is a family of genetic elements capable of eliciting, in transfected cells, a cellular surface antigen which is correlated with human chronic lymphocytic leukemia (CLL). Its prototype member, HSAG-1, was cloned as a 3.4 kb insert and contains numerous Alu-related elements, including its left hand 1.4 kb antigen-eliciting end. These elements are present in mammalian cells with copy numbers varying from 7,000 to 200,000 per haploid genome, depending on how closely their sequence conforms to the Alu consensus sequence. They are present in the configuration found in HSAG-1, a 3.4 kb EcoRI fragment which is part of a larger unit of at least 12.7 kb, at a frequency of 20-50 per haploid genome, and dispersed around the genome. A second family member, HSAG-2, isolated using a functional assay, was cloned as a 9.5 kb insert and contained a 1.5 kb antigen-eliciting left hand end. As in HSAG-1, the antigen-eliciting portion of the insert also contained Alu-like elements, unlike most of the remainder of the insert. A number of HSAG family members were cloned from a library of human CLL genomic DNA by sequence homology with the antigen-eliciting portion of HSAG-1. Most of these members were also shown to be capable of eliciting antigen. Their only sequence similarity with HSAG-1 appeared to be in their content of numerous Alu-like elements. The evidence thus supports the view that the HSAG functional family consists of clusters of Alu-like elements.